Upaya Meningkatkan Kepercayaan Diri Siswa Melalui Kegiatan Muhadhoroh - Sandhika Anggun Awaliyani; Anis Kholifatul Ummah (Indonesian Publication Center, 2021)
Self-confidence is a very important part of the development of the student's personality, which will be the driving force and determinant of how these students behave and behave. In essence, every student has self-confidence, but between one student and another student the confidence they have is different. Some have low self-confidence and some have high self-confidence. The low self-confidence is caused by many factors, and to overcome it, efforts are needed to help increase this self-confidence. One of these efforts is by holding muhadhoroh activities. Referring to this statement, the researcher is interested in conducting literature study research to identify efforts to increase student self-confidence through muhadhoroh activities. The research method used is literature study by examining several references or writings (literacy) that are relevant to the topics discussed. The results of this study indicate that through muhadhoroh activities can help increase students' self-confidence. With muhadhoroh activities, it will train students to have the ability to speak in public so as to form the mentality of these students.